Analysis of Meituan’s Competitive Strategy in the Hotel and Travel Service Market Based on Porter’s Five Forces Model - Zhou, Chan (Transactions on Economics, Business and Management Research, 2024)
As digital transformation accelerates, Online travel services have become the mainstream way for modern consumers to choose travel products and services. China’s online travel services market is expanding rapidly, as China’s leading online service platform, Meituan’s hotel and travel service sector has performed outstandingly in the industry, but at the same time it faces fierce market competition and rapidly changing consumer demands. Therefore, this study uses Porter’s Five Forces Model analysis tool, taking Meituan’s hotel and travel sector as the research object, this paper analyzes Meituan’s current advantages and existing competitive threats from five aspects, including the bar-gaining power of suppliers and customers, competition within the industry, and the threat of new entrants and substitute products. Finally, based on the competitive environment of the online travel service market and Meituan’s current competitive disadvantages, corresponding optimization measures and suggestions are proposed to provide support for Meituan’s strategic decision-making in order to maintain and enhance Meituan’s market position.